A High‐Power Aqueous Zinc–Organic Radical Battery with Tunable Operating Voltage Triggered by Selected Anions. Issue 9 (27th February 2020) - Luo, Yuwen; Zheng, Feipeng; Liu, Luojia; Lei, Kaixiang; Hou, Xuesen; Xu, Gang; Meng, Hui; Shi, Jifu; Li, Fujun
Abstract: In contrast to traditional rechargeable rock‐chair metal‐ion batteries, dual‐ion batteries (DIBs) involve redox reactions with anions rather than cations in p‐type cathodes. In principle, regulating the electrochemical performance of the DIB by different anion species is highly feasible. Herein, the anion effect on the electrochemical performance of a DIB, the aqueous Zn– organic radical battery (Zn‐ORB), consisting of a poly(2, 2, 6, 6tetramethylpiperidinyloxy‐4‐yl vinyl ether) cathode and a Zn anode, was investigated by DFT calculations. SO4 2−, CF3 SO3 −, and ClO4 − with different molecular electrostatic potential values were selected as anion models. DFT calculations revealed that a stronger electrostatic interaction of the anion with the organic radical resulted in a higher operating voltage of the Zn‐ORB, which was consistent with experimental results. These results bring new insight into the redox chemistry of p‐type organic radicals with anions and will promote the development of high‐power aqueous Zn‐ORBs as well as inspire more investigations into the anion effect towards novel battery designs. Abstract : Tunable operating voltage : The anion effect induces a varied redox ability of p‐type organic radicals, leading to tunable operating voltage of Zn–organic radical batteries. DFT calculations reveal that the stronger interaction of the anion with the organic radical host, the higher the operating voltage of the Zn–organic radical battery.